Efeitos do uso de m-Health na motivação e práticas alimentares de indivíduos com hipertensão - Fauro, Milena Uriarte (2022)
Arterial hypertension (AH) is a multifactorial chronic non-communicable disease (NCD), dependent on genetic/epigenetic, environmental and social factors, with obesity and advanced age being the main risk factors for its development. Healthy eating patterns have been associated with reduced blood pressure (BP) and food motivation is a determinant of individuals' food choices. The use of mobile health (m-Health) applications can strengthen non-pharmacological approaches in the treatment of AH. The general objective of this research was to evaluate the effects of the use of m-Health on food motivation and eating practices of individuals with AH treated in the Primary Health Care (PHC) network. This is a controlled, non-randomized, non-blinded clinical trial. Data were collected at enrollment and 12 weeks after the intervention with an m-Health application, called Monitora PA. This study is part of the integrative project Sistema e-lifestyle: an e-Health solution for monitoring the health conditions of hypertensive patients, approved in the MS-SCTIEC-Decit/CNPq nº 12/2018 – Research on innovation in health. Sociodemographic data were collected, the level of knowledge about AH was assessed using the Hypertension Knowledge- Level Scale (HK-LS), dietary practices through the Food Guide for the Brazilian Population questionnaire, food motivation using The Eating Motivation Survey and conducted a clinical evaluation. Initially, 63 individuals participated in the research, 34 in the control group (CG) and 29 in the intervention group (IG). However, at the end of the 3 months, 18 participants returned in the CG and 19 in the IG. Most were elderly, from economic class C. Participants in both groups were overweight at the beginning of the research and also after the 12 weeks of intervention. Regarding dietary practices, there was no statistically significant difference between the initial and final means, and the final values of the CG were lower than the initial values of the GI. When evaluating the individuals' food motivation, it was observed that in the IG there was a statistically significant reduction in the variables habits, preference, need, pleasure and emotions. In the CG, the reasons for food choices increased in the variables health and weight control. Furthermore, the individuals had good knowledge about AH since the pre-intervention, with no statistically significant difference after the intervention time. The Monitora PA application proved to be efficient for changing food motivation related to the habits, preference, need, pleasure and emotions of individuals. More studies involving the use of m-Health in hypertensive individuals are needed.